UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN SAMBUNG NYAWA (Gynura procumbens (Lour.)Merr.) TERHADAP BAKTERI Bacillus cereus ATCC 6633 - Cut Masyithah Thaib; Zuhairiah Zuhairiah; Artha Yuliana Sianipar; Eta M. Br Simanullang (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
Life-sustaining plants are plants that are widely used by people as natural medicines. Infectious disease is one of the problems in the health sector. Infection can be caused by various microorganisms, one of which is bacteria. This research was conducted at the Microbiology Laboratory, Sari Mutiara University, Indonesia. This study was conducted to examine the antibacterial activity of the ethanolic extract of life-sustaining leaves using the paper disc diffusion method with concentration variants of 20%, 30%, 40%, 50%, and 60% and used a negative control of DMSO and positive control of chloramphenicol. From the research that has been done, the extract of the continued life leaves has antibacterial inhibitory power. At a concentration of 20% (10 mm). At a concentration of 30% (11 mm). At a concentration of 40% (12.67 mm). At a concentration of 50% (13.3 mm). At a concentration of 60% (15.3 mm). It can be concluded that the ethanolic extract of the grafted life leaves has the highest antibacterial inhibition at a concentration of 60%, which is 15.3 mm.